Pengaruh tanaman semusim terhadap pertumbuhan jati - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1992)
To investigate the ecology of tumpangsari system practised in Java, teak (Teclona grandis L.) was grown in 1986 at Compartment 17, Wanagama I, Yogyakarta, along with rice (Oryza sativa L.), corn (Zea mays L.), and peanut (Arachis hypogea L.) in plots with and without legume (Acacia glauca L.). Observation during this period showed that the effect of acacia was not significant, similar to that when teak was 4 and 16 month old. The N-total content of the soil increased, but statistically was not significant. The type of crop significantly influenced .the performance of teak, although the difference between teak grown with rice and peanut was not significant. The order of positive companionship of crops on teak was rice, peanut, corn.